Self-Training Through Rumah Pendidikan for Teachers at State Senior High School 1 Tapung Hilir - Nurmainnah; Maya Novita Sari (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the implementation of independent training through the Rumah Pendidikan platform for teachers at SMA Negeri 1 Tapung Hilir in supporting digital transformation in education. The study employed a descriptive qualitative approach involving the principal, vice principal for curriculum, and eight subject teachers selected through purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that independent training through the Rumah Pendidikan platform contributes positively to improving teachers’ digital competence, creativity, confidence, and innovation in technology-based learning. Teachers increasingly utilized interactive presentations, digital quizzes, video learning, and online assessment tools in classroom activities. However, several challenges remained, including unstable internet access, unequal digital competence, limited technological facilities, and teachers’ workload. The school addressed these issues through mentoring, monitoring, motivation, and strengthening digital learning facilities. Therefore, sustainable support is needed to optimize digital-based professional development for teachers.